The Impact of Online Learning toward Students’ Academic Performance on Business Correspondence Course - Berlinda Mandasari (EDUTEC : Journal of Education And Technology, 2020)
Covid-19 pandemic becomes global issue that gives global impact in all sectors especially in educational one. The Minister of Education and Culture of Indonesia make a policy in which all education sectors are shifted from face-to-face learning into online learning. This policy is well-responded by one of private universities in Lampung. The researcher conducted a research to response this policy. The objective of this study is identify the impact of online learning toward students’ academic performance on Business Correspondence course. Participants of this study are 40 students (14 male and 26 female) who enrolled Business Correspondence course at English Education study program of Universitas Teknokrat Indonesia. The design of this research is descriptive qualitative. Data were collected through questionnaire that consists of 22 statements and open-ended interview. The result showed that online learning has positive impact on students’ academic performance in term of learning motivation, learning achievement and learning engagement. Participants also showed that conducting online learning is relevant during pandemic. Furthermore, flexibility, accessibility, learning autonomy, and boosting students’ achievement become the strengths of conducting online learning. However, financial issue and bad internet access become problems that hamper online learning.